PERSEPSI MAHASISWA TERHADAP PEMBELAJARAN BAHASA INGGRIS - Raynesa Noor Emiliasari; E. Kosmajadi (MADINASIKA, 2019)
This research aims to examine descriptively about students' perceptions of learning English. The research method used is descriptive quantitative survey techniques. The population consists of students who have attended English courses in the last two years, with total sampling techniques. The data source is primary data, analyzed using a descriptive statistical approach to find out the frequency of answers and the percentage magnitude. The results of the study prove that the students' perspective on learning English is not optimal. Learning English is considered heavy, inadequate environment and facilities.